The Source of Business Profits - Walker, Francis A. (Quarterly Journal of Economics, 1887)
Journal Article The Source of Business Profits Get access Francis A. Walker Francis A. Walker Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 3, April 1887, Pages 265–288, https://doi.org/10.2307/1882759 Published: 01 April 1887